Rol del maestro en la realidad educativa actual - Guerrero Rivera, Yoselin (2016)
The current education in Peru presents several problems which affect the full development of the potential of students. Nevertheless, teachers must understand them as starting points to plan our work in classrooms. First, it is important for teachers to be clear about the guideline we will follow to apply several strategies and methods in our ongoing pedagogical practice. Secondly, strategies must be applied that allow us to capture the student's attention and guide him towards the development of his capacities. Thirdly, it is important to develop in them not only the cognitive part, but also the emotional and creative part. Only in this way will we be able to form young people for the future.